Comunicação alternativa e ampliada e os caminhos para formação em terapia ocupacional - Biancolli, Luana Gonçalves (Universidade Federal de São Carlos, 2020)
The literature points out that difficulties in oral communication or the impossibility of performing it can cause occupational dysfunctions that hinder the activities of daily life. Meeting or minimizing this limitation is the main purpose of Alternative and Augmentative Communication (AAC), which is one of the areas of Assistive Technology (AT). The objective of this work was to describe the path taken in the theme of Assistive Technology, more specifically the AAC during the graduation of Occupational Therapy and studies developed during this process. To this end, three activities developed in the area will be described, one being a first study to map possible AAC users in the municipal school system and two other studies with procedures for implementing resource systems with children with cerebral palsy. The results of this path were the realization of two Scientific Initiations, two presentations and a submission of derivative work for congresses in the area of Assistive Technology, a report of experience in an extension project and the elaboration of an article for a specialized journal. This trajectory with Alternative and Augmentative Communication provided me with a broader and more complex view of individuals and their particularities. During the graduation years, I went through the steps described in the literature and during the course on the relationship between the Occupational Therapist and the AAC, which was fundamental for my personal and professional growth.
Augmentative and alternative communication and the paths to training in occupational therapy
Keywords: Tecnologia assistiva; Comunicação Alternativa; Terapia Ocupacional; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL